KAJIAN KEAMANAN PANGAN PADA INDUSTRI PENGOLAHAN SUSU DI JAWA TENGAH DENGAN MENGGUNAKAN METODE GOOD MANUFACTURING PRACTICES (GMP) - Adi, Prakoso; Mulyani, Rizka; Khabibah, Lutfia Nur (Jurnal Teknologi Industri Pertanian, 2023)
The milk processing industry is a company engaged in the processing of pure milk into processed products, such as pasteurized and homogenized milk. Efforts are being made to guarantee the quality of the milk product is of good quality, safe, and in accordance with the quality standards expected by consumers, the processing business unit requires an appropriate quality management system; one of which is through the application of the concept of Good Manufacturing Practices (GMP). The objective of this study was to assess the food safety of pasteurized milk production in relation to the adoption of Good Manufacturing Practices (GMP) within the milk processing sector in Central Java. The method used were to collect data directly (interviews and observations), collect data indirectly (literature study, documentation and data), and carry out direct practice activities. Observations were made based on the Regulation of the Minister of Industry of the Republic of Indonesia Number 75/M-IND/PER/7/2010 concerning Guidelines for Good Manufacturing Practices (GMP) covering 18 concepts, namely: location, building, sanitation facilities, machinery and equipment, materials, supervision of processes, final products, laboratories, employees, packers, product labels and descriptions, storage, maintenance and sanitation programs, transportation, documentation and disassembly, training, product recalls, and implementation of guidelines. The results of the study show that it can be concluded that CV CN has complied or complied with the principles and procedures for the correct processing method and has been declared very satisfactory and declared feasible. Keywords: food safety, good manufacturing practices, evaluation, dairy processing